A case of cardiac sarcoidosis mimicking cardiac amyloidosis on cardiovascular magnetic resonance. (5th February 2018) - Takemura, Kazunori; Nakamura, Ryuta; Shimazu, Kazuhito; Sugimoto, Youichiro; Takase, Tetsuro; Ryogo, Minamimoto; Hiroe, Michiaki
Abstract: A 52‐year‐old male visited our hospital with abnormal electrocardiogram and exertional fatigue. The electrocardiogram showed first‐degree atrioventricular block, complete right bundle branch block, and inverted T waves in Leads II, III, aVF, V3, and V4. Echocardiography showed biventricular wall thickening involving granular sparkling of the interventricular septum. Late gadolinium enhancement on cardiovascular magnetic resonance (CMR) was found at the circumferential right ventricular wall and patchy regions of the left ventricle. Although these findings strongly suggested cardiac amyloidosis, he was finally diagnosed with systemic sarcoidosis due to the following. First, endomyocardial biopsy revealed non‐caseating epithelioid granuloma with giant cells. Second, 18 F‐fluorodeoxyglucose positron emission tomography showed uptake in bilateral hilar lymph nodes, para‐aortic lymph nodes, and the biventricular wall of the heart. Although echocardiography and CMR are very useful tools for diagnosis of cardiomyopathies, their specificity and accuracy need to be considered.